Neurodidactic teacher training program for educational dropouts in vulnerable groups - Claudia De Barros Camargo; Carmen Flores Melero; Cristina Pinto Díaz; Cristina Marín Perabá (Frontiers in Education, 2023)
Neurodidactic is presented as an effective teaching tool for creating an equitable society, regardless of the population. This educational methodology, which has recently been introduced in teacher training, supports students with functional diversity, special educational needs, sensory diversity (visual or auditory), and those belonging to the Gypsy ethnic group. Neurodidactics emphasizes that the teacher's role is to create synapses in the neuronal structures through activities that a student finds innovative, attractive, and motivating. To achieve this, it is necessary to identify the aspects that should be included in the training of teachers to work with students who belong to vulnerable groups and to develop effective intervention programs based on neurodidactics. The study population comprises professors of higher education at the University of Jaen (UJA) who responded to a Likert scale survey using an operationalization table. The survey was conducted to determine the professors' knowledge of neuroscience, particularly neurodidactics.